2016
DOI: 10.1002/ijc.29966
|View full text |Cite
|
Sign up to set email alerts
|

Infectious mononucleosis, other infections and prostate-specific antigen concentration as a marker of prostate involvement during infection

Abstract: Although Epstein-Barr virus has been detected in prostate tissue, no associations have been observed with prostate cancer in the few studies conducted to date. One possible reason for these null findings may be use of cumulative exposure measures that do not inform the timing of infection, i.e., childhood versus adolescence/early adulthood when infection is more likely to manifest as infectious mononucleosis (IM). We sought to determine the influence of young adult-onset IM on the prostate by measuring prostat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 46 publications
2
26
0
Order By: Relevance
“…Together with findings for genitourinary tract infections, these results suggest that many types of infections may influence the prostate, either directly through prostate infection or indirectly through possible mechanisms such as local genitourinary‐ or systemic inflammation‐mediated cell damage, leading to chronic prostate inflammation. These findings also suggest that the influence of infections may be sustained over a period of at least a few months to 1 year …”
Section: Introductionmentioning
confidence: 68%
See 2 more Smart Citations
“…Together with findings for genitourinary tract infections, these results suggest that many types of infections may influence the prostate, either directly through prostate infection or indirectly through possible mechanisms such as local genitourinary‐ or systemic inflammation‐mediated cell damage, leading to chronic prostate inflammation. These findings also suggest that the influence of infections may be sustained over a period of at least a few months to 1 year …”
Section: Introductionmentioning
confidence: 68%
“…In contrast to the above‐described direct prostate‐specific mechanism for PSA elevation, mechanisms for non‐genitourinary, systemic infections, such as varicella, are likely less direct. We previously proposed that these infections may contribute to elevated PSA by several possible mechanisms, including systemic inflammation‐mediated prostate cell damage and increased vascular permeability, or increased vascular permeability in the context of preexisting prostate epithelial cell damage/disruption from other sources . In addition, once infection has resolved, PSA could possibly remain elevated for months to years later for a number of reasons, including chronic inflammation against residual infectious antigens, continued healing, delayed or impaired ability to counteract future prostate insults, or broken tolerance to self‐prostatic antigens, all of which could possibly amplify with repeated infections over time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A small number of studies demonstrate a correlation between other infectious causes and an increase in PSA. For instance, Epstein‐Barr virus (EBV), a herpes family virus and the causative agent of infectious mononucleosis (IM), has been associated with a PSA rise as well . One case‐control study of a population of US military recruits with or without IM found a statistically significant increase in the probability of large PSA increase (defined as an increase by 20 ng/mL or 40% or greater rise) in those diagnosed with IM compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…every 3 months ( Figure 1) and was seen clinically every 6 months. His PSA values were as follows: 3.38 (May 2013), 3.15 (July 2013), 1.71 (October 2013), 3.15 (January 2014), 2.72 (Apr 2014), 2.05 (June 2014), 2.40 (October 2014), 2.43 (December 2014); his PSA velocity had been flat ( Figure 1). In April 2015, his PSA value was markedly elevated at 7.61. Review of systems revealed that the patient was recently diagnosed with shingles.…”
Section: Casementioning
confidence: 99%